Bottom-up synthesis of fully sp2 hybridized three-dimensional microporous graphitic frameworks as metal-free catalysts. Issue 24 (7th June 2017) - Talapaneni, Siddulu Naidu; Kim, Jaehoon; Je, Sang Hyun; Buyukcakir, Onur; Oh, Jihun; Coskun, Ali
Abstract : We demonstrated template-free inclusion of the third dimension into the graphitic frameworks while retaining π-conjugation and conductivity, which was verified by their activity as metal-free electrocatalysts for the hydrogen evolution reaction. Abstract : We report on the bottom-up synthesis of a fully sp 2 -hybridized nitrogenated three-dimensional microporous graphitic framework (3D-MGF) starting from a highly preorganized, saddle-shaped tetraphenylene derivative under ionothermal reaction conditions. The 3D-MGF showed high stability and a surface area of 928 m 2 g −1 along with a narrow pore size distribution. Our approach enabled template-free inclusion of the third dimension into the graphitic frameworks while retaining π-conjugation and conductivity, which was verified by their activity as metal-free electrocatalysts for the hydrogen evolution reaction.